Does direct democracy increase civic virtues? A systematic literature review - Bernhard, Laurent (Frontiers in Political Science, 2024)
Due to widespread citizen disenchantment with representative democracy, the introduction of direct-democratic institutions is often promoted as a promising remedy to overcome the current democratic crisis. Theorists of participatory democracy have argued that direct democracy can foster civic virtues, given that the opportunity to participate in referendums and initiatives is generally expected to empower and enlighten citizens. By conducting a systematic literature review, this article aims to provide an overview of scholarship on how direct democracy delivers on its promise to increase individual civic virtues. To that end, it focuses on the effects of direct democracy on those four areas to which scholars have devoted much attention so far: (1) electoral turnout, (2) external and internal efficacy, (3) political knowledge, and (4) subjective wellbeing and satisfaction with democracy. Based on 67 selected studies, it turns out that there is only little positive overall effect of direct democracy on civic virtues, with a great deal of variation. The empirical analysis establishes a negative time trend, indicating that researchers have increasingly reported negative findings over the years. This main result calls into question the expectations advanced by the theorists of participatory democracy and gives some credit to more skeptical views. This review concludes by providing scholars with new avenues for research.